CHARACTERISTIC OF SALEH BAY COASTLINE - Yulius Yulius; Muhammad Ramdhan; Ardiansyah Ardiansyah (Jurnal Segara, 2018)
Indonesia is an archipelagic country with numbers of natural resources including bays. As a closed estuary, bay has a strategic role as one of the ecological resources and environmental services. Saleh Bay is an outstanding bay of West Nusa Tenggara province which is situated between Sumbawa regency and Dompu regency. The study aimed to explain the criteria for the determination of a bay based on UNCLOS and bathymetry system by using Geographic Information System (GIS). The results of the identification indicated that the Ocean Map issued by Dishidros had not entirely referred to the criteria of UNCLOS in determining an area as a bay, in which an indentation is regarded as a bay if its total area is larger than the area of t he semi-circle whose diameter is a line drawn across the mouth of that indentation. Subsequently, spatial analysis found out that the depth of the waters in Saleh Bay can be classified into eleven classes, which are: (1) 0 – 10 meter with area of 294.27 km2, (2) 10 - 20 meter with area of 205.45 km2, (3) 20 - 30 meter with area of 259.45 km2, (4) 30 - 40 meter with area of 146.25 km2, (5) 40 - 50 meter with area of 137,83 km2, (6) 50 - 60 meter with area of 148.19 km2, (7) 75 - 100 meter with area of 57.08 km2, (8) 100 - 150 meter with area of 73.78 km2, (9) 150 - 200 meter with area of 109.46 km2, (10) 200 - 300 meter with area of 533.42 km2 , and(11) >300 meter with area of 134.89 km2.